2009
DOI: 10.1002/bies.200900066
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete penetrance and variable expressivity: is there a microRNA connection?

Abstract: Incomplete penetrance and variable expressivity are non‐Mendelian phenomena resulting in the lack of correlation between genotype and phenotype. Not withstanding the diversity in mechanisms, differential expression of homologous alleles within cells manifests as variations in penetrance and expressivity of mutations between individuals of the same genotype. These phenomena are seen most often in dominantly inherited diseases, implying that they are sensitive to concentration of the gene product. In this framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 77 publications
0
35
0
Order By: Relevance
“…10 We showed that a significantly high number of IP-VE genes are targeted by multiple miRNAs and are co-expressed with the cognate miRNA in the same tissue. Meta-analysis of data from the public domain indicates a negative correlation between the miRNA and target protein levels.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…10 We showed that a significantly high number of IP-VE genes are targeted by multiple miRNAs and are co-expressed with the cognate miRNA in the same tissue. Meta-analysis of data from the public domain indicates a negative correlation between the miRNA and target protein levels.…”
Section: Introductionmentioning
confidence: 88%
“…Meta-analysis of data from the public domain indicates a negative correlation between the miRNA and target protein levels. 10 Our analysis indicated that SNP in the miRNA target site can potentially affect its interaction with miRNA based on the predictions using dbSMR database, which utilizes structural parameters associated with variation. 16 For our current study, we selected 2 IP-VE genes-namely, JAG1 and TGFBR2-from a list of 88 genes previously predicted as targets of miRNA mediated regulation.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…When the SNP locus is in the 'seed' region of a miRNA, the stability of the mRNA-miRNA interaction may be altered by this polymorphism. 27 RNAhybrid (http://bibiserv. techfak.uni-bielefeld.de/rnahybrid) predicts the secondary structure and minimum free energy (MFE) of the entire micro-RNA:mRNA duplex.…”
Section: Selection Of Snps In the Mirna Target Site Of Scrc-related Gmentioning
confidence: 99%
“…The pre-microRNA is then transported out of the nucleus to the cytoplasm by the nuclear export complex composed of Exportin 5 and RAN. In the cytoplasm, the Dicer complex further cuts the pre-microRNA into its mature form; the mature microRNA is functional as part of the RISC (Ryan et al 2010;Ahluwalia et al 2009). …”
Section: Microrna Biogenesismentioning
confidence: 99%